2009
DOI: 10.1253/circj.cj-08-0917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pitavastatin on Fasting and Postprandial Endothelial Function and Blood Rheology in Patients With Stable Coronary Artery Disease

Abstract: Pitavastatin significantly improved fasting and postprandial dyslipidemia and endothelial dysfunction in CAD patients, partly via reducing oxidative stress and increasing plasma adiponectin, although rheological parameters remained unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 55 publications
(71 reference statements)
1
17
0
Order By: Relevance
“…Pitavastatin treatment in long-term smokers was associated to reduced LDL-C oxidation and protection of endothelium from oxidative stress (Yoshida et al, 2010). In patients with stable CAD, pitavastatin ameliorated postprandial endothelium-dependent vasodilation, inhibiting oxidative stress (Arao et al, 2009). Moreover, pravastatin and fluvastatin had a direct scavenging radical activity Kassan et al, 2010).…”
Section: B Statins and Endothelial Functionmentioning
confidence: 99%
“…Pitavastatin treatment in long-term smokers was associated to reduced LDL-C oxidation and protection of endothelium from oxidative stress (Yoshida et al, 2010). In patients with stable CAD, pitavastatin ameliorated postprandial endothelium-dependent vasodilation, inhibiting oxidative stress (Arao et al, 2009). Moreover, pravastatin and fluvastatin had a direct scavenging radical activity Kassan et al, 2010).…”
Section: B Statins and Endothelial Functionmentioning
confidence: 99%
“…156 In addition, it has been shown that pitavastatin 2mg/ day may result in reduction of both postprandial hypertriglyceridemia and endothelial dysfunction in obese subjects and in patients with stable coronary artery heart disease. 157,158 Simvastatin 80mg has also been seen to be effective in reducing postprandial plasma triglyceride levels and triglyceride-content in lipoprotein fractions in male obese patients with metabolic syndrome. 159 …”
Section: Statinsmentioning
confidence: 99%
“…25, 26 In brief, examinations were performed in a quiet, dark, temperature-controlled (22-24°C) room. Subjects rested for at least 15 min before the examination.…”
Section: Vascular Endothelial Functionsmentioning
confidence: 99%